Response of human oral mucosal epithelial cells to different storage temperatures: A structural and transcriptional study. - Mazyar Yazdani; Aboulghassem Shahdadfar; Sjur Reppe; Dipak Sapkota; Evan M Vallenari; Majlinda Lako; Che J Connon; Francisco C Figueiredo; Tor Paaske Utheim (PLoS ONE)
Purpose Seeking to improve the access to regenerative medicine, this study investigated the structural and transcriptional effects of storage temperature on human oral mucosal epithelial cells (OMECs). Methods Cells were stored at four different temperatures (4°C, 12°C, 24°C and 37°C) for two weeks. Then, the morphology, cell viability and differential gene expression were examined using light and scanning electron microscopy, trypan blue exclusion test and TaqMan gene expression array cards, respectively. Results Cells stored at 4°C had the most similar morphology to non-stored controls with the highest viability rate (58%), whereas the 37°C group was most dissimilar with no living cells. The genes involved in stress-induced growth arrest (GADD45B) and cell proliferation inhibition (TGFB2) were upregulated at 12°C and 24°C. Upregulation was also observed in multifunctional genes responsible for morphology, growth, adhesion and motility such as EFEMP1 (12°C) and EPHA4 (4°C-24°C). Among genes used as differentiation markers, PPARA and TP53 (along with its associated gene CDKN1A) were downregulated in all temperature conditions, whereas KRT1 and KRT10 were either unchanged (4°C) or downregulated (24°C and 12°C; and 24°C, respectively), except for upregulation at 12°C for KRT1. Conclusions Cells stored at 12°C and 24°C were stressed, although the expression levels of some adhesion-, growth- and apoptosis-related genes were favourable. Collectively, this study suggests that 4°C is the optimal storage temperature for maintenance of structure, viability and function of OMECs after two weeks.